Neural systems for auditory perception of lexical tones. (February 2016) - Kwok, Veronica P.Y.; Dan, Guo; Yakpo, Kofi; Matthews, Stephen; Tan, Li Hai
Abstract: Previous neuroimaging research on cognitive processing of speech tone has generated dramatically different patterns of findings. Even at the basic perception level, brain mapping studies of lexical tones have yielded inconsistent results. Apart from the data inconsistency problem, experimental materials in past studies of tone perception carried little or minimal lexical semantics, an important dimension that should not be dispensed with because speech tones serve to distinguish lexical meanings. The present study sought to examine the neural correlates of the perception of speech tone using lexically meaningful experimental stimuli. A simple lexical tone perception task was devised in which native Mandarin speakers were asked to judge whether or not the two syllables of an auditorily presented Chinese bisyllabic word had the same tone. We selected bisyllabic words as experimental stimuli because Chinese monosyllables often convey little or very vague meanings due to rampant homophony. We found that the left inferior frontal gyrus, the right middle temporal gyrus and bilateral superior temporal gyri are responsible for basic perception of linguistic pitches. Our interpretation of the data sees the left superior temporal gyrus as engaged in primary acoustic analysis of the auditory stimuli, while the right middle superior temporal gyrus and the left inferior frontal region are involved in both tonal and semantic processing of the language stimuli. Highlights: The present study sought to examine the neural correlates of the perception of speech tone. We used lexically meaningful stimuli, because the major role of speech tones is to distinguish lexical semantics. Left inferior frontal gyrus, right middle temporal gyrus, and bilateral superior temporal gyri are crucial regions.